Implementasi Kebijakan Peraturan Daerah No.2 Tahun 2012 Kota Semarang Dengan Studi Retribusi Pelayanan Pasar Di Kota Semarang (Studi Kasus Pasar Karangayu) - Muhammad Iqbal Sudrajat; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Market retribution’s service is an effort that Semarang Local Government do to increase the income Original Local Government Revenue of Semarang City. The importance of collecting the local retribution in Semarang city is an effor of local government in directing tax’s collect and dicipline in administration, tight controll along with that chance to participate in giving founding to society to raise their awareness in paying the retribution and pay attention for the things that influence retribution’s acceptance. In this research, writer choose the case about implementation of market retribution’s service in Karangayu Market, Semarang City. The method used in this research is qualitative – descriptive type, with informants form Head of Income Section in Trade Department Semarang City, Technical Implementing Service Unit of Karangayu Market, Head od Karangayu Market that concern in market retribution’s service policy in Karangayu Market dan the seller in Karangayu Market. The purpose of this research are for analyze about implementation of market retribution’s service and it is analyzed using 5 accuracy theory by Riant Nugroho, and describe the factors that influence results the policy’s implementation using Edward III theory. The result of the research shown that in the implementation of market retribution’s policy that implemented in Karangayu Market, there are some problems which is about facilities and service which isn’t good yet; the rejection from seller that not fully suporting the market retribution’s service policy. The constraint factors are about the resources, the rejection from the seller in Karangayu Market and the tax levied which still not appropiate with the SOP. The reccomendation earned from this research are; the local government doing intensify’s socialization, the addition of the resources, correcting tax system of retribution, and giving more education to the seller in Karangayu Market